Biodiversity–ecosystem function experiments reveal the mechanisms underlying the consequences of biodiversity change in real world ecosystems. (29th June 2016) - Eisenhauer, Nico; Barnes, Andrew D.; Cesarz, Simone; Craven, Dylan; Ferlian, Olga; Gottschall, Felix; Hines, Jes; Sendek, Agnieszka; Siebert, Julia; Thakur, Madhav P.; Türke, Manfred
Abstract: In a recent Forum paper, Wardle ( Journal of Vegetation Science, 2016) questions the value of biodiversity–ecosystem function (BEF) experiments with respect to their implications for biodiversity changes in real world communities. The main criticism is that the previous focus of BEF experiments on random species assemblages within each level of diversity has 'limited the understanding of how natural communities respond to biodiversity loss.' He concludes that a broader spectrum of approaches considering both non‐random gains and losses of diversity is essential to advance this field of research. Wardle's paper is timely because of recent observations of frequent local and regional biodiversity changes across ecosystems. While we appreciate that new and complementary experimental approaches are required for advancing the field, we question criticisms regarding the validity of BEF experiments. Therefore, we respond by briefly reiterating previous arguments emphasizing the reasoning behind random species composition in BEF experiments. We describe how BEF experiments have identified important mechanisms that play a role in real world ecosystems, advancing our understanding of ecosystem responses to species gains and losses. We discuss recent examples where theory derived from BEF experiments enriched our understanding of the consequences of biodiversity changes in real world ecosystems and where comprehensive analyses and integrative modelling approaches confirmed patterns found in BEF experiments. Finally, we provide some promising directions in BEF research. Abstract : In a recent Forum paper, Wardle ( Journal of Vegetation Science, 2016) questions the value of biodiversity–ecosystem function (BEF) experiments. While we appreciate that new and complementary experimental approaches are required for advancing the field, we describe how BEF experiments have identified important mechanisms that play a role in real world ecosystems, advancing our understanding of ecosystem responses to species gains and losses. Figure modified after Isbell et al. (2013).